The coast of giants: an anthropometric survey of high schoolers on the Adriatic coast of Croatia - Grasgruber, Pavel (PeerJ, 2019)
The aim of this anthropometric survey was to map regional differences in height and body proportions in eight counties adjacent to the Adriatic coast of Croatia. Body height was measured in 1,803 males and 782 females aged 17–20 years at 66 schools in 23 towns. When corrected for population size in regions, mean male height is 182.6 cm in all eight counties, 182.8 cm in seven counties of Adriatic Croatia, and 183.7 cm in four counties of Dalmatia proper. Regional variation is considerable: from 180.6 cm in the county of Karlovac to 184.1 cm in the county of Split-Dalmacija. The mean height of females is based on more limited data (168.0 cm in seven counties). These results show that young men from Dalmatia are currently the tallest in the world in the age category of 18 years, and the north-to-south gradient of increasing stature on the Adriatic coast largely mirrors that in neighbouring Bosnia and Herzegovina (BiH). The extraordinary values of height in Croatia and BiH can most likely be explained by unique genetic predispositions that are shared by the local populations of the Dinaric Alps.